Co-pyrolysis of Hardwood Combined with Industrial Pressed Oil Cake and Agricultural Residues for Enhanced Bio-Oil Production - P. Madhu; L. Vidhya; S. Vinodha; Shiny Wilson; S. Sekar; Pravin P. Patil; S. Kaliappan; S. Prabhakar (Journal of Chemistry)
Lignocellulosic biomass is the potential raw material for the production of biofuels through pyrolysis. It is an effective technique for converting biomass to biofuels. However, biofuel from agricultural residues and woody-based feedstocks shows poor fuel properties due to higher oxygen content. Co-pyrolysis is a promising process to produce high-quality bio-oil by two or more different materials. Forestry, industrial, and agricultural outcomes are the ideal co-feedstocks for improved bio-oil quality. In this study, individual and co-pyrolysis of hardwood, pressed mustard oil cake and corncob were conducted at a temperature of 500°C. Before conducting pyrolysis experiments, thermogravimetric analysis was conducted to evaluate thermal degradation behavior. Through individual pyrolysis, corncob yielded a maximum bio-oil of 43.9 wt%. On the other hand co-pyrolysis on binary blends of hardwood and corncob produced maximum bio-oil of 46.2 wt%. Compared to individual pyrolysis, the binary blend produced more bio-oil, suggesting a synergistic effect between hardwood and corncob. The decreased bio-oil yield of 40.1 wt% during co-pyrolysis of ternary blends suggests negative synergistic effects prejudiced by the volatiles available in the biomass mixture. The improved quantitative synergistic results in the co-pyrolysis process give crucial information for the development of feed-flexible, higher bio-oil production and clean operating systems. The characterization studies on bio-oil by Fourier transform-infrared spectroscopy (FTIR), gas chromatography–mass spectrometry (GC-MS), and 1H NMR spectroscopy have shown that the bio-oil is a combination of aliphatic and oxygenated compounds. The analysis of the heating value shows that the bio-oil can be utilized as a fuel for heating applications.